Economic Development and Regional Inequality: Origins of the Brazilian Case - Leff, Nathaniel H. (Quarterly Journal of Economics, 1972)
I. Emergence of the disparity, 244. — II. Differences in rates of regional export growth, 245. — III. Some questions, 248. — IV. Earlier explanations, 249. — V. An interpretation of the decline of Brazilian sugar and cotton exports, 252. — VI. Land and imperfect factor reallocation, 255. — VII. The exchange-rate mechanism under imperfect factor reallocation, 255. — VIII. Currency-area effects and regional divergence, 258. — IX. Conclusions, 260.